The Rise and Fall of the Islamic Empire and the Threat to the West - Nergis Mazid (International Institute of Islamic Thought, 2003)
Historians and literary critics looking for examples of modern literature using classic Orientalist discourse will find The Rise and Fall of the Islamic Empire and the Threat to the West a useful tool. Anthony J. Dennis presents 1,400 years of history, interprets the Qur'an and the Shari'ah, scrutinizes Sunni and Shi'a sectarianism, psychoanalyzes Muslims, comments on the status of women, discusses international political and national movements, and gives diplomatic and military contingency plans for civilians and policymakers to stem the "Islamic threat" to the West in 157 pages (including notes). His second edition forward begins with a polite "I-told-you-so" claiming that 9/11 occurred because Americans were not as vigilant as he told them to be in his first edition (1996), that it was the "first chapter in what promises to be a long battle" (forward) between Islam and the West. According to the author, the fall of communism ended the cold war system of checks and balances and allowed rogue Islamic states to flourish. Iran, being one of the oldest rogue states and an established enemy of the United States, took the USSR's place in stimulating and directing revolutions. Given that Muslims are religiously directed to hate all nonMuslims and western prosperity is a reminder of their shortcomings, Muslims are jealous and eager to embrace the new revolution ...